Factors affecting adherence to pharmacotherapy in parkinson's disease - Shivaansh Aggarwal; Gunchan Paul; Birinder S Paul; Diksha Mahendru; Shriya Goyal (Annals of Indian Academy of Neurology, 2021)
Background: The goal of dopaminergic replacement therapy to achieve good clinical outcome in Parkinson's disease (PD) patients largely depends on the pattern of adherence to the pharmacological treatment. This study aims to find the factors affecting medication adherence in patients with PD keeping in mind the cultural, economic, and social diversities so that preventive steps can be taken to fill these gaps.Methods: Demographic data, disease parameters, treatment-related factors, family characteristics, educational, and employment status were assessed for relationship with the medication adherence pattern in a cohort of non-demented PD patients. Medication adherence was measured by MMAS-8; depression, and socioeconomic status were assessed by GDS-SF and Kuppuswamy scales respectively. Results: From 134 PD subjects, high adherence was observed in 43.2%, 18.2% had moderate, and 38.6% reported low adherence level to their pharmacotherapy. The sub-optimal level of adherence was significantly correlated to compliance of follow up with the physician (p 0.03), presence of adverse events related to drugs (p 0.03), and depressive symptoms (p < 0.0001). Also, there was significant negative co-relationship between poor adherence and depression on Spearman's rank coefficient (0.702). There was no effect of demographic factors, living conditions, family type, educational qualification, associated comorbid conditions, and socioeconomic status on adherence to dopaminergic treatment in patients with PD. Conclusion: Poor adherence to prescribed medication is a menace that is more than just oversimplification of forgetfulness which should be evaluated at each visit to improve efficacy of the prescribed regimen to achieve better treatment result and thus quality of life of PD patients.